Peningkatan Peran Serta Suami/Keluarga dalam Mendukung Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Jekan Raya Palangka Raya - Heti Ira Ayue; Oktaviani Oktaviani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The coverage of exclusive breastfeeding in Palangka Raya City is also far from the target set by the government. Palangkaraya Health Profile in 2017 from 10 main Puskesmas in Palangka Raya City, the three lowest coverage health centers was Jekan Raya Health Center (2.58%), Menteng Health Center (6.13%), and Kayon Health Center (9.42%). The purpose of this community service is to provide assistance to improve the role of the husband in supporting exclusive breastfeeding in the Jekan Raya Community Health Center in Palangka Raya City. The community service was carried out three times to target pregnant/postpartum mothers and their husbands/families.